Estimating the impact of economic globalization on economic growth of Ghana: Wavelet coherence and ARDL analysis - Samuel Tawiah Baidoo; Bright Tetteh; Elliot Boateng; Raphael Edem Ayibor (Research in Globalization, 2023)
Considering the importance of economic globalization in shaping Ghana's economic growth trajectory, examining the relationship between these two variables is crucial for policymakers to develop strategies aimed at maximizing the benefits of economic globalization and minimizing the challenges associated with it. Therefore, this study investigates the long-run and short-run effects of economic globalization on economic growth of Ghana. The autoregressive distributed lag (ARDL) is employed for the analysis. This paper further employs the Phillips-Oliar's residual-based cointegration test and the continuous wavelet coherence test to examine the causality between economic growth and its determinants. The results from the ARDL model suggest that economic globalization has not promoted economic growth. Specifically, a 1% increase in economic globalization reduces economic growth by 1.80% and 3.90% in the short- and long run periods respectively at a 1% significance level. The results further reveal capital, government expenditure and labour as key determinants of economic growth. The wavelet causality test reveals a one-way causality from economic growth to economic globalization. Based on the findings, policy suggestions have been highlighted for stakeholders' consideration with the aim of enhancing economic growth of Ghana.
Keywords: 330; Economic globalization; Economic growth; Ghana; Wavelet coherence test